Replacing silkworms Tubifex sp. with fermented paste feed enriched with curcumin on Asian redtail catfish Hemibagrus nemurus larvae growth - Heltonika, Benny; Aryani, Netti; Asiah, Nur; Lesmana, Indra; Nuraini, Nuraini; Harefa, Firman Theodali (Jurnal Akuakultur Indonesia, 2026)
To maintain growth and survival, Asian redtail catfish postlarvae require silkworms as live food. However, due to their extreme sensitivity to natural conditions, silkworms will be exceedingly scarce during the rainy season. This study aimed to evaluate fermented commercial feed enriched with curcuminas replacement of silkworms for the growth and survival of redtail catfish postlarvae. This study employed a complete design experiment consisting of six treatments: P1 (non-fermented commercial feed), P2 (no curcumin-enriched fermented commercial feed), P3 (curcumin-enriched fermented commercial feed at 0.35 g/kg), P4 (curcumin-enriched fermented commercial feed at 0.70 g/kg), P5 (curcumin-enriched fermented commercial feed at 1.05 g/kg), and P6 (silkworms). Each treatment was replicated four times. The Asian red tail catfish postlarvae, measuring 0.63 ± 0.05 mm in length, were cultivated at a density of 5 fish/L. Fish were raised for a period of thirty days. Growth in total weight, total length, specific weight rate, specific length rate, and survival rate of postlarvae were the parameters measured. The growth evaluation results indicate that substituting silkworm feed with fermented feed supplemented with curcumin at a concentration of 1.05 g/kg resulted in growth of 6.66% (length) and 14.29% (weight) lower than the silkworm treatment (P